Redesain Ruang Kelas Menggunakan Metode Human Centered Design pada Kasus: UPTD SDN Cinere 1 Depok - Muhammad Faiz R; Ibnu Burhan Jabbar; Muhammad Fahri Rasyid; Reza Phalevi Sihombing (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
SDN Cinere 1, located on Jalan Cinere Raya, Depok City, is a local government-owned educational building that has experienced a decline in physical quality due to its aging, no longer meeting the standards for appropriate learning facilities. This situation prompted the need to design a new school building capable of providing a safe, comfortable, and appropriate learning environment that meets current learning needs. This study aims to assess user needs by examining student and teacher experiences during classroom activities as a basis for implementing a Human-Centered Design (HCD) approach. The research method used a descriptive qualitative approach through observation, interviews, and questionnaires. The results of the study revealed key issues related to spatial comfort, layout flexibility, lighting, and limited support for interactive learning. Based on these findings, a learning space concept oriented toward user comfort, adaptability, and interaction was formulated. This study concludes that the HCD approach is effective in designing elementary school classrooms to optimally support student creativity and interaction.